Functional Morphology of the Human Uterine Tubes in the 21st Century: Anatomical Novelties and Their Possible Clinical Applications - Varga, I; Csöbönyeiová, M; Visnyaiová, K; Záhumenský, J; Pavlíková, L; Feitscherová, C; Klein, M (Physiological research, 2022)
The uterine tube (UT) pathologies account for 25-35% of female factor infertility. Although these peculiar organs were first studied several hundred years ago, they have become overlooked and neglected mainly due to the successes of reproductive medicine. Nevertheless, the reproductive medicine still faces many challenges regarding the fertility outcomes of in vitro fertilization (IVF). Many obstacles and problems can be resolved by a more detailed understanding of the UT morphology and function during normal reproduction. Over the course of the 21st century, many new insights have been obtained: the presence of a population of telocytes in the tubal wall responsible for normal motility and hormone sensory function, the demonstration of lymphatic lacunae of the mucosal folds necessary for oocyte capture and tubal fluid recirculation, or a thorough profiling of the immune makeup of the UT epithelial lining with the discovery of regulatory T cells presumably important for maternal tolerance towards the semi-allogenic embryo. New discoveries also include the notion that the UT epithelium is male sex hormone-sensitive, and that the UT is not sterile, but harbors a complex microbiome. The UT epithelial cells were also shown to be the cells-of-origin of high-grade serous ovarian carcinomas. Finally, yet importantly, several modern morphological directions have been emerging recently, including cell culture, development of tubal organoids, in silico modelling, tissue engineering and regenerative medicine. All these novel insights and new approaches can contribute to better clinical practice and successful pregnancy outcomes.
Keywords: Fertilization in Vitro; fertilizace in vitro; vejcovody; Pregnancy; těhotenství; fertilita; Fertility; Male; lidé; Female; mužské pohlaví; ženské pohlaví; Epithelium; epitel; Humans; Ovary; ovarium; Fallopian Tubes